Transparency in cinema; opacity in literature: the scripted writing of Eu receberia as piores notícias dos seus lindos lábios, by Marçal Aquino - de Oliveira, Marília Corrêa Parecis [UNESP] (2024)
This article proposes an analysis of the novel Eu receberia as piores notícias dos seus lindos lábios, by Marçal Aquino (2005). The study aims to analyze the aesthetic and semantic effects resulting from the “script-like writing” employed by the author in constructing the literary narrative. The term “script-like writing” is used by Schøllhammer (2009) to designate Brazilian literary production beginning in the 1990s, characterized by narratives that employ techniques analogous to audiovisual and digital media. Therefore, the perspective adopted here not only concerns comparing two different languages, namely literature and cinema, to explore how writing itself corroborates elements of a language associated with iconic technology.